DYNAMICS OF ORGANIZATIONAL COMMUNICATION IN URBAN INFRASTRUCTURE OF MEDAN CITY GOVERNMENT: DEVELOPMENT IMPLICATIONS IN THE FRAMEWORK OF MODERNIZATION AND EQUALITY OF ACCESS - Ritonga, Hasnun Jauhari; Mansur, Awal (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to explore the dynamics of organizational communication in the management of urban infrastructure projects in Medan City, focusing on how communication between institutions and with the community affects the success of infrastructure development. The urgency of this research arises from the need to address complex urban problems such as congestion and flooding, as well as support sustainable and inclusive city modernization efforts. The methodology used in this study is qualitative with a descriptive approach, where primary data is collected through archives and official documents published by the Medan City Government, including details of project implementation and progress reports. Secondary data involves relevant literature studies to strengthen the analysis of organizational communication dynamics. Data analysis was carried out using the Miles, Huberman, and Saldana model which includes data collection, condensation, display, and drawing conclusions from data. The results of the study indicate that the effectiveness of organizational communication plays a critical role in ensuring the success of infrastructure projects, especially in supporting equal access and encouraging modernization. Projects such as the Mebidang Bus Rapid Transit (BRT) and the construction of the Jalan Gatot Subroto underpass not only improve mobility but also open wider access to city services, contributing to a more equitable distribution of development benefits. In the discussion, this study suggests the importance of strengthening communication structures and adopting new communication technologies to improve transparency and responsiveness in project management.